1990
DOI: 10.1016/0272-0590(90)90057-q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhaled azodicarbonamide on F344/N rats and B6C3F1 mice with 2-week and 13-week inhalation exposures*1

Abstract: Azodicarbonamide (ADA), a compound used in the baking and plastics industries, has been reported to cause pulmonary sensitization and dermatitis in people. Two-week repeated and 13-week subchronic inhalation exposures of F344/N rats and B6C3F1 mice to ADA were conducted to determine the toxicity of inhaled ADA. The mean air concentrations of ADA in the 2-week studies were 207, 102, 52, 9.4, or 2.0 mg/m3. No exposure-related mortality nor abnormal clinical signs were observed in rats or mice during or after exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In this study, a concentration-related decrease in weight gain and food intake was observed in rats that are fed ADA-containing food, suggesting that the inclusion of ADA in the diet was associated with a reduction in the food consumed by the rats and a corresponding decrease in body weight. While one previous study had reported no significant effect of ADA on body weight [ 21 ]; the result of another study revealed that acute (14 days) but not chronic (13 weeks) inhalational exposure to ADA resulted in a decrease in body weight at the highest dose administered ADA [ 22 ], (similar reduction in body weight was observed in this study in the second week). The duration of exposure in this study was 28 days and the route of administration was oral; the effects that we observed suggest that the effect of ADA was dependent on both route of administration and duration of exposure.…”
Section: Discussionsupporting
confidence: 73%
“…In this study, a concentration-related decrease in weight gain and food intake was observed in rats that are fed ADA-containing food, suggesting that the inclusion of ADA in the diet was associated with a reduction in the food consumed by the rats and a corresponding decrease in body weight. While one previous study had reported no significant effect of ADA on body weight [ 21 ]; the result of another study revealed that acute (14 days) but not chronic (13 weeks) inhalational exposure to ADA resulted in a decrease in body weight at the highest dose administered ADA [ 22 ], (similar reduction in body weight was observed in this study in the second week). The duration of exposure in this study was 28 days and the route of administration was oral; the effects that we observed suggest that the effect of ADA was dependent on both route of administration and duration of exposure.…”
Section: Discussionsupporting
confidence: 73%
“…In male rats, the high dose (10% azodicarbonamide) at the end of the study showed only mild growth depression with a corresponding decrease in food intake. Similarly, the absence of a significant effect of 2-week repeated and 13-week subchronic inhalation exposure to azodicarbonamide on the final weight of rats is indicated in the results of Medinsky et al (1990), and in the highest exposure group, final body weight was slightly reduced. In the present study, the addition of different doses of azodicarbonamide to the diet with excessive fat content did not lead to a significant change in the body weight of the animals.…”
Section: Figurementioning
confidence: 86%
“…The change in relative organ mass under the influence of azodicarbonamide was described in a study by Medinsky et al (1990). Thus, 2-week inhalation exposure to azodicarbonamide at a dose of 200 mg/m 3 caused a decrease in the mass of the liver of male rats, but no macro-or microscopic lesions of the organ were detected.…”
Section: Figurementioning
confidence: 89%
“…Flour-related products make up a large portion of a family’s dietary structure in many countries, and the whiteness and gluten of flour can be improved by incorporating additives to meet the actual demand. Azodicarbonamide (ADA), which was employed initially as a foaming agent of rubber articles dating back to 1940, now has been widely used in the flour industry as a bleaching agent, gluten fortifier, or dough conditioner in many countries. ADA itself has low acute toxicity and also does not react directly with flour; however, it can react with moist flour as an oxidizing agent to convert into biurea (BIU) and semicarbazide (SEM), which were reported to have genotoxicity in vitro and carcinogenicity, under a high temperature environment such as baking. Therefore, chronic consumption of flour-related products, which contain excess ADA, will cause severe harm to humans . Thus, the maximum allowable level of ADA in flour has been set to 45 mg/kg (ppm) in the United States, Canada, and Asia, and some regions and countries such as the European Union and Australia have even banned its utilization in flour. To control the effectiveness of these legal provisions and to ensure the safety of flour-related products for consumption, it is highly crucial to establish a simple method for the rapid and on-site detection of ADA in flour.…”
mentioning
confidence: 99%